PENGARUH KOMPENSASI TERHADAP MOTIVASI KERJA KARYAWAN PADA PT GRACIA UTAMAJAYA SEMARANG - Jumiyati, Jumiyati (Jurnal Akrab Juara, 2018)
Abstract Compensation should not be ignored if the company wants qualified and highly motivated employees. This research uses observation method, questionnaire method and literature study method by using quantitative descriptive. Data analysis used is correlation coefficient test, coefficient of determination test and regression equation with calculation using SPSS version 21 program application. The sampling technique used is saturated sampling of 37 respondents in PT Gracia Utamajaya Semarang. The results of this study indicate that the compensation positive relationship on employee motivation with the correlation coefficient of 0.761 is included in the strong category. While the effect of compensation with motivation obtained by 57.9% the rest influenced by other factors, while the test results of regression equation obtained value Y = 14.824 + 0.632X identifies that if no compensation done by the company, the motivation will be 14.824 units. And vice versa if the compensation of 0.632 states that each addition of 1 unit of compensation will increase employee work motivation of 0.632.